DNA barcoding confirms the validity of Anthidium melanopygum Friese, 1917 stat. nov. (Hymenoptera: Megachilidae) as a distinct species of Western Asia - Kasparek, Max; Fateryga, Alexander V. (Zootaxa, 2023)
Heinrich Friese described Anthidium spiniventris [sic] from Palestine in 1899, and A. melanopygum as a “variety” of it from Turkey in 1917. While A. melanopygum was subsequently recognized as a subspecies of A. spiniventre, a morphological examination of new material of both taxa suggests that these taxa represent distinct species. This was also confirmed by genetic barcoding of the mitochondrial cytochrome c oxidase subunit 1 (COI) gene, which revealed the two taxa form distinct clades with an average genetic distance of 5.69%, while the genetic within-group distance of these two taxa was only 0.14% for A. melanopygum and 0% for A. spiniventre. Anthidium melanopygum has a wide distribution that extends from Greece and Bulgaria in the west across Turkey and Iran to Turkmenistan in the east. By contrast, A. spiniventre has a restricted, disjunct distribution with isolated populations in the southern Levant and Iran.